Development of the mon busquets pass, an audio-based football passing instruments for kids aged 10 to 12 - Suhermon, Suhermon; Hendryanto, Ferri; Putra, Rizki Wijaya; Satriadi, Adi (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: The lack of an updated football passing measurement tool is the issue with this study. Purpose: Developing an audio-based football passing assessment tool for kids aged 10 to 12 is the goal of this project. Method: Research and development (R&D) is the methodology used in this study. Thirty School Football (SSB) players made up the population and sample in this study. On June 13, 2024, one material expert and one media expert were given questionnaires as part of the research. Two tests for the instrument's reliability will be passed on July 5, 2024, and July 7, 2024. The Criteria Test uses the results of the football passing comparison test carried out on July 6 2024 to determine the validity of the test. Data collection methods using questionnaires and tests. Results: The research results were obtained from 93% material experts and 87% media experts. Validity 0.91 and reliability 0.89, indicating validity and reliability based on Kirkendall's categories. Conclusion: Apart from that, it is also hoped that this Regular Beginner Lecturer Research (PDP) activity can meet the Main Performance Indicators / IKU 2 (Students Gain Experience Outside Campus) and IKU 3 (Lecturers Have Activities Outside Campus). Coaches and athletes feel happy and enthusiastic about the existence of this football passing instrument and this instrument can be disseminated widely as a measuring tool to see football passing ability. There are advantages to this product, including requiring equipment that is easy to obtain and a weakness in this product, namely that there is no automatic technology that gives the ball to the testee who will carry out the test.